Effects of an icon-based menu labelling initiative on consumer food choice. (January 2017) - Kerins, Claire; Cunningham, Katie; Finucane, Francis M; Gibson, Irene; Jones, Jenni; Kelly, Colette
Aims: The purpose of this study was to examine the impact of an icon-based menu labelling initiative on consumer buying behaviour. Methods: This quasi-experimental study recruited a convenience sample of eight food service establishments, all with at least one menu item meeting the heart healthy criteria. Data from sales of all menu items sold over an 8-week period were collated 4 weeks prior to and 4 weeks during the display of information icons related to healthy food choices on menus. Results: The absolute change in menu item sales showed a non-significant trend towards an increase in healthier menu item selections. Furthermore, there was no association between the type of food service establishment and the percentage change in labelled menu item sales. Conclusion: The study did not find a statistically significant influence of the icon-based menu labels on consumer food choice. Given the limited amount of research that examines alternative menu labelling formats in real-world settings, more studies are necessary to confirm these results. Further research is needed to identify the optimal format, content and impact of menu labels on consumer behaviour.